Group dynamics and drama in education in dialogue: Or: The backstage is where the magic happens! (Pedagogical Horizons, 2025)
Two social fields in interdisciplinary dialogue. This article focuses on the synthesis of theoretical perspectives on the concept of “role” from the view of drama in education and group dynamics. It explores the extent to which concepts from group dynamics and drama in education can help educators reflect on their own role and thereby expand their professional competence. Two case studies in the context of teacher training and school development consulting provide helpful practice-oriented approaches. The interest in dialogue on this topic is rooted in the long-standing collaboration between the two authors. Both are united by their work in and with groups and their theoretical and practical engagement with the concept of “role.”
Keywords: drama education; group dynamics; professionalization; role; role concept